Globalne i lokalne scenariusze dla edukacji ze zmianą społeczną w tle - Anna Pogorzelska (Edukacja Ustawiczna Dorosłych)
The changes that affect almost all areas of modern man's life mean that he is faced with challenges that no one has experienced before. Hence, great hopes are placed on education and its institutions, where young generations will be prepared for changes in the future. Unfortunately, as stated by a large group of educational experts, the Polish school remains in the old pattern of functioning and does not meet the needs of young generations. Therefore, the necessary and urgent task of Polish education is to search for new educational models in which the student will not only be able to use their creative potential and their strengths, but also overcome their own limitations and weaknesses. The educational scenarios presented in the text were inspired by the following reports: OECD Schooling Scenarios in Brief 2007; Poland 2030, 2009; Education of the Future, 2020, et al.